System of activities for the development of critical thinking in secondary school students (Praxis Educativa, 2021)
The study presents the results of the main author's master's thesis. Critical thinking is considered a cultural construction, therefore, it requires education and cultivation. The analysis of research on critical thinking shows multiple possibilities to favor its development, highlighting the use of creativity; however, there are still limitations in teachers and students. Thus, the objective is to present the design of a system of creative activities that contribute to the development of critical thinking. The scientific methods that are part of the investigation are of the empirical, theoretical and statistical level. Dimensions and indicators of critical thinking that served as a guide for obtaining the scientific result were considered. These confirm the effectiveness of the system of creative activities to develop critical thinking in students as the students managed to analyze the information, infer implications, propose alternative solutions and argue the positions assumed.